2004
DOI: 10.1093/geront/44.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Fit and Strong Intervention on Older Adults With Osteoarthritis

Abstract: These benefits indicate that this low-cost intervention may hold great promise as one of a growing number of public health intervention strategies for older adults in the United States with osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
227
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(243 citation statements)
references
References 24 publications
13
227
2
1
Order By: Relevance
“…Health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al 2008), better functional, physical, and psychosocial health (Taylor et al 2004;Hughes et al 2004), more positive affect (Netz et al 2007), reduced risk of falling (Carter et al 2001), better health-related quality of life (Rejeski and Mihalko 2001;Motl and McAuley 2009), and less cognitive decline (Klusmann et al 2010). However, despite this evidence, many older adults are not sufficiently active to enjoy these health benefits (Newsom et al 2004).…”
Section: Physical Activity and Health In Old Agementioning
confidence: 99%
“…Health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al 2008), better functional, physical, and psychosocial health (Taylor et al 2004;Hughes et al 2004), more positive affect (Netz et al 2007), reduced risk of falling (Carter et al 2001), better health-related quality of life (Rejeski and Mihalko 2001;Motl and McAuley 2009), and less cognitive decline (Klusmann et al 2010). However, despite this evidence, many older adults are not sufficiently active to enjoy these health benefits (Newsom et al 2004).…”
Section: Physical Activity and Health In Old Agementioning
confidence: 99%
“…Six studies reported analysis of attrition including race/ethnicity, with 1 showing greater attrition from the intervention study for nonwhites (22) and 5 showing no differences based on race/ethnicity (21,26,28 -30). Two of these studies (29,30) reported no differences in attrition, comparing responders and nonresponders on demographic characteristics without explicitly stating that they examined race. However, race was one of their demographic characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The data from one of those trials were presented in two complementary articles 46,47 and the data from another trial were used in four articles [42][43][44][45] . Six health economic evaluations [48][49][50][51][52][53] were identified. No review was identified in which the included studies fulfilled the inclusion criteria.…”
Section: R Resultsmentioning
confidence: 99%
“…In Germany, cancer rehabilitation typically is reimbursed. It is mostly offered as inpatient care and would need to be provided as outpatient treatment as well to increase flexibility 53 . In other countries such as Italy, however, cancer rehabilitation is hardly implemented yet 47 .…”
Section: Cancer Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation